Malaria Infection as a Leading Cause of Febrile Seizures among Children with Seizures in Ekiti State University Teaching Hospital, Ado Ekiti, Nigeria - Oke, Oluwasola Julius; Ajite, Adebukola; Oluwayemi, Oluwadare Isaac; Olatunya, Oladele Simeon; Ogundare, Ezra Olatunde; Abdulraheem, Fadlulai Olaoluwa (Journal of Pediatric Neurology, 2019)
Febrile seizure (FS) is among the leading cause of pediatric admissions in developing countries. The etiologic patterns of FS among children attending Pediatric Emergency of Ekiti State Teaching Hospital in Ado Ekiti were studied. A prospective study of children who had FS was carried out. A prevalence of 2.9% was found and malaria was the leading cause of FS in 111 (85.4%) patients. Seventy-eight (60%) of the 130 patients with FS had their seizure occurring within the first 24 hours of onset of fever. Malaria was the most common cause of fever precipitating FS in the index study. Prevention of malaria and prompt management of fever will reduce the prevalence and improve the outcome of FS. The overall prevalence of FS is similar to developed countries and the etiology is similar to other studies from Nigeria.
Keywords: patterns; febrile seizure; etiology; malaria